Plasticity plays a dominant role in regulating the phenological variations of sugar maple populations in Canada - Guo, Xiali; Buttò, Valentina; Mohytych, Vasyl; Klisz, Marcin; Surget-Groba, Yann; Huang, Jianguo; Delagrange, Sylvain; Rossi, Sergio (Frontiers in Ecology and Evolution, 2023)
Global changes affect the growing conditions of terrestrial ecosystems, causing a mismatch between plant phenology and local climates in Northern regions. Due to their long lifespan and irregular regeneration periods, trees cannot respond quickly enough to climate variability through long-term genetic adaptation. In this study, we explored the phenological plasticity and genetic variation among populations of bud burst in sugar maple (Acer saccharum Marsh.) seedlings from 30 Canadian provenances with contrasting climates planted in two common gardens near and at the northern limit of the species’ range. We tested the hypothesis that phenotypic plasticity and genetic variation among populations affect bud phenology. We expect that phenotypic plasticity is more important in regulating bud phenology due to the high variability in short-term weather events characterizing this part of North America. Bud development and leafing occurred in April-May, with complete bud burst lasting between 21 and 29 days. On average, bud swelling differed by 12 days between common gardens. Both factors site (common gardens) and provenance significantly affected bud burst, demonstrating phenological plasticity and genetic variation of sugar maple, respectively. A significant interaction between site and provenance was also found. Overall, the site (11.8-90.3%) contributed more than provenance (0-3.1%) to the variance in timings of bud burst, indicating a dominant role of plasticity in regulating spring phenology. Our study demonstrated the concurring effects of genetic variation and phenological plasticity of sugar maple and revealed the dominant role of the latter factor. The high plasticity observed in sugar maple has a crucial role in the phenological adaptation of maple and the survival of its local populations in a context of changing climate.